Evaluation of Obesity with Vitamin D Levels and Related Parameters - Aybike Gizem Kayacan; Neslihan Sürmeli; Mehtap Ünlü Söğüt; Elanur Yılmaz (Erciyes Medical Journal, 2019)
Objective: This study aimed to investigate the relationship between vitamin D levels, biochemical findings, and body analysis data of adult individuals, and effects of seasonal vitamin D level differences on these relationships. Materials and Methods: In this retrospective study, medical records of 159 individuals who applied to Samsun Büyük Anadolu Hospital Nutrition and Dietary Polyclinic were examined. The serum 25(OH)D levels were defined as <10 ng/ml vitamin D deficiency; 10–20 ng/ml vitamin D insufficiency; and >20 ng/ml normal vitamin D level. Vitamin D levels were also divided into two according to seasons: summer and winter. Results: Of the 159 participants included in the study, 42 were overweight and 94 were obese. Vitamin D deficiency was found in 21.4% and vitamin D insufficiency was found in 35.2% of the patients. Winter vitamin D levels were significantly lower than summer vitamin D levels. Vitamin D levels decreased with increasing body fat mass and percentage, abdominal fat mass and percentage. Individuals with vitamin D deficiency had higher body mass index than individuals with vitamin D insufficiency. Vitamin B12 levels of individuals with vitamin D deficiency were found to be significantly lower. Aspartate aminotransferase levels of individuals with vitamin D deficiency were higher than individuals with vitamin D insufficiency. Conclusion: Vitamin D deficiency and insufficiency varies according to sunbathing times in summer and winter season and it is quite common in obese patients. Strategies should be developed to prevent and control obesity and to combat the inadequacy of vitamin D nutritional status.